2017
DOI: 10.3390/met7030092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Copper-Based Composites Reinforced by CuZrAlNiTi Amorphous Particles with Enhanced Mechanical Properties

Abstract: Abstract:Novel amorphous/crystalline composites were developed combining the ductile copper matrix with hard CuZr-based amorphous powder. The amorphous powders of two compositions, Cu 39.2 Zr 36 Al l4.8 Ni 10 Ti 10 and Cu 39.2 Zr 35.2 Al 5.6 Ni 10 Ti 10 , produced by ball milling were used for reinforcement of the composites. Different mixing techniques, magnetic mixing, ultrasonic mixing and high-energy ball milling, were applied in order to create a homogenous mixture of the powders. The composites were prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In this process, elemental or alloy powders are subjected to highly energetic impact forces, resulting in the formation of new phases. Various kinds of defects and chemical disorder are introduced into crystalline solids during milling [1,2,3]. It was first performed on Fe-based amorphous alloys by Trudeau et al to explore the structural evolution during milling [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this process, elemental or alloy powders are subjected to highly energetic impact forces, resulting in the formation of new phases. Various kinds of defects and chemical disorder are introduced into crystalline solids during milling [1,2,3]. It was first performed on Fe-based amorphous alloys by Trudeau et al to explore the structural evolution during milling [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similar also been reported for Al matrix composites reinforced with Ni-Nb metallic glass particles [4]. Due to the above-mentioned advantages, it has been shown that metallic glass shows excellent strengthening effects in metals such as aluminum [12,21,24,25], magnesium [26] and copper alloys [27,28]. However, despite the high strengthening effect obtained for aluminum and aluminum alloys by adding MG reinforcement, the ductility of these AMMCs is still relatively low [29].…”
Section: Introductionmentioning
confidence: 68%